Pengaruh model pembelajaran team games tournament (tgt) berbantuan media phet simulation terhadap konsep dasar pecahan pada kelas IV sdn se-kecamatan laweyan - Rahmawati, Septiana Mulia; Istiyati, Siti; Adi, Fadhil Purnama (Universitas Sebelas Maret, 2024)
This research aims to investigate the impact of implementing the Team Games Tournament (TGT) learning model with the assistance of PhET Simulation media on the fundamental understanding of fractions among fourth-grade students at SDN Se-Laweyan District during the academic year 2023/2024. The research design employed is Quasi-Experimental with Nonequivalent Control Group Design. The study sample consists of 47 fourth-grade students from SDN in Laweyan Subdistrict. Test assessments were utilized as the data collection method.The preliminary data analysis included normality and homogeneity tests. The results from the independent sample t-test indicated a significance level of Sig.<0.05 (0.000<0.05), leading to the rejection of H0 and acceptance of H1. In conclusion, this research demonstrates a noteworthy influence of the Team Games Tournament (TGT) learning model, supported by PhET Simulation media, on enhancing the understanding of basic fraction concepts among fourth-grade students at SDN Se-Laweyan District in the 2023/2024 academic year.